Genomic analysis and phytoprobiotic characteristics of Acinetobacter pittii P09: A p-hydroxybenzoic acid-degrading plant-growth promoting rhizobacteria - Liu, Xijian; Sun, Li; Wang, Shuaibing; Pu, Zitian; Cao, Runze; Wu, Shuaishuai; Xie, Zhihong; Wang, Dandan (Environmental technology & innovation, 2025)
p-hydroxybenzoic acid (PHBA), as a representative allelochemical, accumulates in soil and poses significant risks to the growth and development of crops, and this study aims to solve the challenge of PHBA autotoxicity through microbial bioremediation. A novel strain Acinetobacter pittii P09 was isolated from the rhizosphere of peanut, exhibiting highly efficient bioremediation and plant growth-promoting functions. Through whole-genome sequencing (3843,723 bp chromosome, 38.88 % GC content) analysis, the key genomic determinants enabling PHBA degradation and plant-beneficial traits including IAA, phosphate solubilization, and biofilm formation were identified. In addition, the application of strain P09 not only significantly enhanced peanut germination and plant growth, but also augmented the activities of antioxidant enzymes under PHBA stress. Overall, these findings demonstrate that Acinetobacter pittii P09 is a multifunctional plant growth-promoting rhizobacteria capable of alleviating autotoxicity stress and facilitating organic agriculture applications. [Display omitted] •The allelochemicals exhibit pronounced phytotoxicity towards peanuts.•A PHBA degrading strain Acinetobacter pittii P09 was isolated and sequenced.•The genes associated with the biodegradation of PHBA has been identified.•The application of P09 alleviated the stress caused by PHBA in peanut.